Maintenance works for the common area at Seri Baiduri Apartment, Shah Alam, Selangor / Muhammad Zuhdi Ahmad - Ahmad, Muhammad Zuhdi (Universiti Teknologi MARA UiTM,Perak, 2022)
PMC Facilities & Real Estate Sdn Bhd formerly known as PMC Property Services was established in the year 2012 and has managed more than 80 projects in Malaysia. PMC has been incorporated to suit the present and future services encompassing property management services, property consultancy services, and real estate agency services. PMC is a licensed property consultancy company registered under the Board of Valuers, Appraisers, Estate Agents and Property Managers Malaysia. It is bound by the Rules and Regulation, Guidelines and Code of Conduct set by the Board to provide professional services to clients and to uphold clients’ interest. PMC is run by a group of young, energetic, and experienced entrepreneurs. Members of the company are professionals and graduates from relevant disciplines including valuers, property managers and estate agents.